Pemetaan Penelitian Bisnis Pariwisata Halal: Analisis Bibliometrik Pada Database Scopus - Purwantoro, Arif; Haryanto, Tri; Nurhidayati, Sri Endah (Universitas Negeri Surabaya, 2023)
The largest market share in the post-pandemic era is controlled by Middle Eastern countries, as evidenced by the fact that the football industry currently owns clubs from there. On the other hand, there are also increasing requests from Muslim tourists who want to carry out their lifestyle by religious teachings. The tourism industry must respond by facilitating halal tourism because most Middle Eastern tourists are Muslim. This study aims to map and briefly describe the bibliometrics of the halal tourism business that can be used to examine trends, patterns, and developments. This study used article publication data from the Scopus database from 1997-2023 with the theme